Daun Ntal sebagai Aplikasi Material Kemasan CD Puzzle Game Aksara Bali - Santosa, Ngurah Adhi; Nandaryani, Ni Wayan (Jurnal SASAK : Desain Visual dan Komunikasi, 2023)
Balinese script as the traditional script of the Balinese people is now increasingly being eroded by the times, especially in the field of education. Balinese script learning methods that are still conventional seem serious and monotonous and tend to get boring quickly. So we need learning support media that are more interesting and according to the needs of children aged 6-8 years. Utilizing the positive value of video Games and puzzle type Games, it is hoped that through the creation of Balinese script puzzle Games it can attract children's interest in learning. As a product in the form of a CD, packaging is needed that aims to protect, increase sales value and show the identity of the product inside. This study uses the method of collecting observational data, documentation and literature study. The design method used is Exploration, Improvisation and Formation of Alma Hawkins. This design produces a Balinese Script puzzle Game packaging that utilizes Ntal leaves as a media application to write information on the Game and add a Balinese identity to the packaging.